Sacred Feminine: A Decolonial Reading of the Indus Mother Goddess and Gandhara Hariti - Jalil Khan (Journal of Religion and Decoloniality, 2026)
This article examines the colonial and patriarchal framing of female divinities in South Asian archaeology, using two case studies: the Indus Valley Mother deity figurines and the Gandhara deity Hariti. Both types of artifacts, which are currently housed in prominent European institutions such as the British Museum, and the Metropolitan Museum of Art, were often overlooked in colonial scholarship and museum catalogues. While the Mother Goddess figurines were reduced to rudimentary "fertility idols" and the Hariti sculptures were demoted to secondary mythological significance in Buddhist art, masculine figures like as the Priest-King, Buddhas, and Bodhisattvas were exalted as vital to South Asian religious tradition. This interpretive hierarchy reflects the complex interplay of colonial epistemologies and patriarchal beliefs that determined how South Asian religious traditions were represented abroad. Using a decolonial feminist lens, the study reinterprets these artifacts as essential religious icons representing feminine spirituality, protection, and fertility, contesting their erasure in colonial and patriarchal narratives. The article demonstrates how decolonial feminist readings of the Indus Mother Goddess and Hariti can restore the significance of female divinities while also contributing to more inclusive interpretations of religion, heritage, and museum practice.